Improving Precise Point Positioning Performance Using Multi-Frequency Multi-Constellation GNSS - Deo, Manoj Nilesh (Curtin University, 2019)
The main drawback of Precise Point Positioning (PPP) is a long convergence time. This thesis integrates Multi-Frequency Multi-Constellation (MFMC) GNSS data to improve PPP convergence. The biases that occur during data integration were identified and modelled. Triple-frequency data was used to improve both float ambiguity and integer ambiguity resolution PPP models. Precise atmospheric products were investigated for constraining the ionosphere and troposphere errors. A method was proposed for maintaining decimetre accuracy during communication outages.